2014
DOI: 10.1111/sjop.12170
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological test norms controlled for physical health: Does it matter?

Abstract: The objective of the present study was to investigate the effects of physical health on neuropsychological test norms. Medical and neuropsychological data from 118 healthy volunteer controls, aged 26-91 years, were collected during five recruitment occasions. The examinations included a clinical investigation, brain neuroimaging, and a comprehensive neuropsychological test battery. Test-specific statistical regression-weights for age, education and gender were calculated to establish preliminary test norms. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
5
12
2
Order By: Relevance
“…The increases in normative scores due to the control for health status displayed no consistent pattern related to level of education. This finding seems inconsistent with the finding in the recent study (Bergman & Almkvist, 2015) where the control for health slightly reduced negative influences of low education. In both studies, however, the effect of the control for health on the impact of education was very small, suggesting that the impact of education on cognitive test scores largely holds up against agerelated morbidity.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The increases in normative scores due to the control for health status displayed no consistent pattern related to level of education. This finding seems inconsistent with the finding in the recent study (Bergman & Almkvist, 2015) where the control for health slightly reduced negative influences of low education. In both studies, however, the effect of the control for health on the impact of education was very small, suggesting that the impact of education on cognitive test scores largely holds up against agerelated morbidity.…”
Section: Discussioncontrasting
confidence: 99%
“…A notable similarity between the findings of the recent study (Bergman & Almkvist, ) and the present one was the relatively high susceptibility to age‐related morbidity of verbal learning and free recall, as measured by the Rey Auditory Verbal Learning test (Lezak et al ., ) in the previous study and SGRC free recall in both studies. The previous study found a susceptibility mainly to the diseases of the circulatory system and in the present one the susceptibility was to global health, implying close to ⅓ SD (residual) in impaired performance at age 80.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations